SEXUAL EDUCATION (SEX-ED) SINCE AS REPRESENTATIVE ACT NUMBER 36 OF 2009 CONCERNING HEALTH TOWARDS REPRODUCTIVE HEALTH PROBLEMS - Amanda Raissa; Astria Yuli Satyarini Sukendar; Tomy Michae (Surakarta Law and Society Journal, 2020)
Adolescent reproductive health problems in Indonesia are increasingly worrying. The high level of adolescent reproductive health problems which is increasingly growing is a serious problem that must be immediately addressed and resolved by the government. This problem certainly has a negative impact on the growth and development of adolescents in Indonesia, especially women. The occurrence of sexually transmitted diseases caused by free sex and ignorance of adolescents about the dangers of free sex is one of the triggers for reproductive health problems for adolescents. Because of this, education is needed for adolescents and even children so that they understand that reproductive health is something that is important for them to protect. Here is the importance of S e x u al E d u c a tio n or (SEX-ED) to provide knowledge, education, and insight to children and adolescents so that they understand more about reproductive health issues, about sexually transmitted diseases (STDs), and about important reproductive matters the other. Because in Indonesia, reproductive health is not studied as a curriculum in schools, and neither at home nor in the environment do many understand sexual education. This is the importance of having to have Sexual Education (SEX-ED) for children and teenagers from an early age. The results of this writing are that there is a need for S e x u al E d u c a tio n (SEX-ED) or the so-called sexual education of adolescent children in Indonesia carried out by the government, the community in the surrounding environment, as well as the participation of parents in order to prevent and overcome the increasing level of reproductive health problems for young people in Indonesia. Keywords: sexual education, reproductive health, adolescents.